1996
DOI: 10.1111/j.1365-2699.1996.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of animals in the colonization of the Krakatau Islands by fig trees (Ficus species)

Abstract: Abstract. Since the biologically extirpating eruption of Krakatau (Sunda Strait) in 1883, Rakata (Krakatau's remnant) and two closely adjacent islands, Sertung and Panjang, have been colonized by over 200 species of vascular plants. They now carry species‐poor mixed tropical forest, including some twenty‐three species of Ficus. Data on the sequence of colonization over the last century by twenty‐four Ficus species, twenty‐three species of volant frugivores, and by agaonid fig‐wasps, presumably from the large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 47 publications
2
35
0
1
Order By: Relevance
“…Shilton et al (1999) demonstrated that small captive pteropodids can retain viable Ficus seeds in their guts for more than 12 hours during the day when they are not feeding; however, because these bats were inactive during this period (Shilton et al 1999), the importance of this result to the long-distance dispersal of seeds is unclear. Nevertheless, the recolonization of the volcanic Krakatau islands by figs and other bat-dispersed taxa clearly demonstrates the importance of fruit bats for the long-distance dispersal of seeds (Whittaker & Jones 1994, Thornton et al 1996, Shilton et al 1999. Although fruit trees and feeding perches may still provide activity foci for most of the seed rain, because many fruit bat species defecate during flight, the overall seed shadows are likely to be relatively extended and more homogeneous compared to those produced for large, uningested seeds (Thomas 1982, Fleming 1988, Utzurrum 1995.…”
Section: Discussionmentioning
confidence: 98%
“…Shilton et al (1999) demonstrated that small captive pteropodids can retain viable Ficus seeds in their guts for more than 12 hours during the day when they are not feeding; however, because these bats were inactive during this period (Shilton et al 1999), the importance of this result to the long-distance dispersal of seeds is unclear. Nevertheless, the recolonization of the volcanic Krakatau islands by figs and other bat-dispersed taxa clearly demonstrates the importance of fruit bats for the long-distance dispersal of seeds (Whittaker & Jones 1994, Thornton et al 1996, Shilton et al 1999. Although fruit trees and feeding perches may still provide activity foci for most of the seed rain, because many fruit bat species defecate during flight, the overall seed shadows are likely to be relatively extended and more homogeneous compared to those produced for large, uningested seeds (Thomas 1982, Fleming 1988, Utzurrum 1995.…”
Section: Discussionmentioning
confidence: 98%
“…For example, transplant experiments of Arnica montana , have revealed that slug herbivory limits the lower elevational range of this subalpine plant (Bruelheide & Scheidel, 1999). Also, the colonization of islands by fleshy-fruited plants provides evidence that range limits and distributional areas of these species strongly depend on animal dispersers (Thornton, Compton & Wilson, 1996; Shanahan et al , 2001). …”
Section: The Role Of Biotic Interactions In Shaping Species' Spatmentioning
confidence: 99%
“…The data of the present study and the other more data (Wang RW et al 2004, unpublished data) indicate that groups of trees are an important unit that keeps the structure of the wasp community stable. As a keystone plant resource in Southeast Asia and the Neotropics, figs support a broad spectrum of vertebrate frugivores during times of food scarcity in these areas (Krebs 1978;Thornton et al 1996;Nason et al 1998;Harrison 2003). Figs greatly affect the function and structure of the tropical rain forest (Sun 1992;Primack 1998) The present study has shown that the effect of fragmentation results in a different structure of the fig wasp community and that such an effect may change the position and function of figs in the fragmented area, thereby resulting in the development of different systems in the process of evolution.…”
Section: Discussionmentioning
confidence: 99%